Credibility and Crisis Stress Testing - Ong, Li (IMF Working Papers; Working Paper ;, 2013)
Credibility is the bedrock of any crisis stress test. The use of stress tests to manage systemic risk was introduced by the U.S. authorities in 2009 in the form of the Supervisory Capital Assessment Program. Since then, supervisory authorities in other jurisdictions have also conducted similar exercises. In some of those cases, the design and implementation of certainelements of the framework have been criticized for their lack of credibility. This paper proposes a set of guidelines for constructing an effective crisis stress test. It combines financial markets impact studies of previous exercises with relevant case study information gleaned from those experiences to identify the key elements and to formulate their appropriate design. Pertinent concepts, issues and nuances particular to crisis stress testing are also discussed. The findings may be useful for country authorities seeking to include stress tests in their crisis management arsenal, as well as for the design of crisis programs.